Penurunan Kadar Trigliserida pada Tikus Jantan dengan Terapi Growth Hormone (DECREASE OF TRIGLYCERIDE LEVEL IN MALE RAT BY GROWTH HORMONE TREATMENT) - Ratnayanti, I Gusti Ayu Dewi; Sugiritama, I Wayan; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made; Mayun, I Gusti Ngurah; Laksemi, Dewa Ayu Agus Sri; Wiryawan, I Gusti Ngurah Sri; Arijana, I Gusti Kamasan Nyoman (Jurnal Veteriner, 2013)
The use of growth hormone (GH) as cardiovascular disease treatment is still controversial. In thispreliminary study the effect of growth hormone therapy on plasma triglyceride level in dyslipidemia wasexamined. Pre and post control group design study was done using 20 dyslipidemic (total cholesterol >200mg/dL) male rats, age 11–12 month-old. The subjects were divided into four groups, aquadest (P0), GH0.02 IU/day (P1), GH 0.04 IU/day (P2), and GH 0.08 IU/day (P3). All subjects were given high cholesteroldiet for three weeks to achieve dyslipidemic in blood level. Aquadest and GH were injected subcutaneouslyonce daily for two weeks. Triglyceride plasma level was measured on day 22nd and 38th by using colorimetricenzymatic test. The mean of pre test plasma triglyceride level of all groups was 136.30 mg/dL and nosignificant difference was found among the groups (p > 0.05). Growth hormone therapy significantly reducedplasma triglyceride level of P1 by 11.78% (118.82 mg/dL, p < 0.01), P2 by 23.46% (103.41 mg/dL, p < 0.01),and P3 by 35.15% (90.22 mg/dL, p < 0.01). Comparison of  post test data amomg the groups showedsignificant difference (p < 0.01). This study show that growth hormone therapy could reduce plasmatriglyceride level in dyslipidemic rat. However, further research is needed to more understand the effect ofthe therapy on cardiovascular diseases.
Keywords: growth hormone, triglyceride, dyslipidemia